Automated 6-minute walk test distance measurement and walk characterisation using a novel infrared sensor-based technique - Isniza Ismail,; Leela T. Narayanan,; Rumaisa Abu Hasan,; Eko Supriyanto, (Penerbit Universiti Kebangsaan Malaysia, 2019)
It is common to use motorised and non-motorised treadmills in settings with space constraints for a 6-minute walk test (6MWT). This test used manual methods which are susceptible to errors. It is believed that automated techniques could eliminate the shortcomings, but this approach was not proposed by any studies. This study presented and analysed the validity of a newly-developed automated infrared-based treadmill walking monitoring system (iTMS), which as specifically designed to measure the distance and characteristics for the walk performance of a non-motorised treadmill 6MWT (nMT6MWT). This study selected 20 subjects for: The validity testing of the iTMS walked distance at five different speeds dictated by metronome beats for 2-minute and at a self-paced speed with intermittent rests for 6-minute, and the characterisation of 6-minute walk performance for distance, speed, acceleration, walking segments, and resting events. The iTMS measured distances were consistently accurate for the varying speeds during the 2-minute walk session. For the 6-minute walk en bloc and its three segments, the difference in distance (Δd) between iTMS (diTMS) and camera recording method (dCRM) showed positive biases with small LOA95% in Bland-Altman plot. The iTMS has an accurate distance measurement with ± 0.20% error of dCRM for en bloc 6-minute walk can characterise the resting events of 0.5 s and more. The iTMS is considered a viable automated method for monitoring distance and characterising nMT6MWT. It also showed the potential in addressing technical errors which may be inherent in manual 6MWT data collection methods.